(untitled) (Scientific journal of the Fergana State University, 2024)
The article provides a literary solution to social issues such as love for the Motherland, the fidelity of woman, family values in the example of an analysis of a poem by the national poet of Uzbekistan Abdulla Sher. In the introductory part, the relevance of the problem is based on the works of leading scientists who expressed their opinion about the poet and the issues they covered. The methodological basis of the article is determined. The “Results and Analysis” section highlights the results of source reviews, the poetʼs literary perception of existence, and personal research using the example of an analysis of "a poem about two women". The scientific conclusions about the study are enumerated at the end of the article.